Head and neck cancer in Brazil - Laís Guedes Alcoforado de Carvalho; Carmellyo Pires Leite Santiago; Ana Cláudia Macedo Andrade; Ana Maria Gondim Valença; Isabella Lima Arrais Ribeiro; Ricardo Dias de Castro (Editorial Ciencias Médicas, 2018)
Introduction: due to its high incidence in Brazil, head and neck cancer requires permanent study of its distribution, which has motivated the conduct of detailed analyses aimed at understanding the way it manifests in the population, its temporal distribution in the country and the main problems it poses. Objective: identify the anatomical locations and histological classifications of head and neck cancers registered in Brazil between the years 2000 and 2014. Methods: an inductive cross-sectional study was conducted with an indirect documentation technique and descriptive statistical processing. The study was based on the analysis of 220 391 secondary data from Cancer Hospital Registries available from the National Cancer Institute. The variables of interest were location of the primary tumor and histological type. Sorting by primary tumor location followed the International Classification of Diseases. Results: the sites most commonly affected by head and neck cancer were facial skin (44.2 %), oral cavity (16.7 %), thyroid gland (8.9 %), larynx (8.8 %), brain (5.4 %) and lymph nodes located in the head and neck region (3.8 %). The most common histological types were squamous-cell carcinoma (38.0 %), basal-cell carcinoma (27.0 %), papillary carcinoma (3.70 %), nodular basal-cell carcinoma (2.50 %) and malignant epithelial tumor (2.50 %). Conclusions: squamous-cell carcinoma was the most prevalent histological type of head and neck cancer between the years 2000 and 2014 in Brazil, facial skin being the most commonly affected site. Keywords: epidemiology; head and neck neoplasms; database.